The Effect of Core Stabilization Exercise on Chronic Low Back Pain Reduction: Critical Review - Wahyuni Wahyuni; Muhammad Afif Robiatul Azis (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
Background: Low back pain (LBP) is a condition of low back pain. Pain that occurs in low back pain is not a disease or a diagnosis but a term for pain that is felt in the affected anatomic area with various variations in the pain duration. In some instances, the initial pain may continue over three months and eventually progress to chronic low back pain (CLBP). Objective: This study was to determine the effect of pain reduction after core stabilization exercise (CSE) on chronic low back pain based on the available literature and to determine the type of core stabilization exercise on chronic low back pain based on the existing literature. Methods: This study used a critical review study. Results: From the results of this study, eight out of 148 articles matched the inclusion criteria. Eight articles were used as the basis for the study, which was continued for the appraisal stage. The appraisal results show that six articles have a Quartile 1 (Q1) value and two articles have a Quartile 2 (Q2) value. The PEDro scale assessment gets seven articles with a low bias (the PEDro score> 5), and 1 article has a high bias (the PEDro score?5). Conclusion: Based on the results of studies that have been conducted on the effect of core stabilization exercise on pain reduction in chronic low back pain, based on studies in the existing literature, it can be concluded that core stabilization exercise affects reducing pain in chronic low back pain.